Sheath-core composite monofilament
Patent Information
- Application Number
- JP2023141022
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-13
AI Technical Summary
【0014】 高精細ハイメッシュフィルタや、高精密印刷用ハイメッシュスクリーン紗に適した、細繊度かつ高強度で、更には整経性及び製織性に優れた芯鞘複合ポリエステルモノフィラメントを提供できる。
Smart Images

Figure 2025034561000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a core-sheath bicomponent polyester monofilament suitable for high-definition high-mesh filters and high-mesh screen gauze for high-precision printing. [Background technology]
[0002] Screen gauze, a gauze fabric made by weaving monofilaments, is used in the electronics field for a variety of applications, including mesh cloth for screen printing on printed circuit boards, as well as molded filters for use in automobiles and mobile phones.
[0003] Specific applications of gauze fabrics woven from monofilaments include, in filter applications, lint filters to prevent dust from re-adhering in washing water, filters installed in air conditioners to remove dust and dirt from indoors, molded filters installed in vacuum cleaners to remove dust and dirt, in the medical field, blood transfusion kits and artificial dialysis circuit filters to remove air bubbles, and in the automotive field, fuel pumps, fuel injection devices and other fuel flow paths, ABS, brakes, transmissions, power steering, etc. In addition, in screen printing applications, T-shirts, banners, signs, vending machine plates, car panels, outdoor and indoor signs, ballpoint pens, various cards, nameplates, scratch cards, Braille, CDs, DVDs, printed circuit boards, plasma displays, liquid crystal displays, etc.
[0004] In filters used in automobiles, mobile phones, etc., there is a demand for smaller filters that are dust-proof and permeable, and so filters are becoming finer. For this reason, finer yarns are required for use as filter yarns.
[0005] In screen printing applications for electronic circuits for home appliances, mobile phones, and personal computers, screen gauze with excellent dimensional stability and little stretch during gauze stretching is required to achieve high printing accuracy. Furthermore, to improve printing accuracy, it is necessary to increase the mesh size of the gauze. In other words, screen gauze raw yarns with high strength and fineness, specifically, a strength of 7.0 cN / dtex or more and a fineness of 13.0 dtex or less, are required.
[0006] On the other hand, it is known that the trade-off between fineness and strength of the raw yarn is the deterioration of the operability of warping and weaving, and various measures have been taken to address this issue.
[0007] In Patent Document 1, a proposal is made to suppress scum during weaving by adopting the form of a core-sheath composite monofilament, disposing a polymer with a lower intrinsic viscosity on the sheath side compared to the core side, and lowering the crystallinity of the yarn surface. In addition, from the viewpoint of achieving both raw yarn strength and weaving properties, the intrinsic viscosity difference between the core and sheath polymers is specified to be 0.15 to 0.30. Although disposing a polymer with a lower intrinsic viscosity on the sheath side certainly suppresses the generation of weaving scum, the examples described in Patent Document 1 have a strength of 6.0 cN / dtex level, and in order to obtain a core-sheath composite monofilament with higher strength, it is necessary to increase the draw ratio or increase the intrinsic viscosity of the core side polymer. When the draw ratio is increased, the fiber orientation on the fiber surface progresses, making the yarn more likely to be scraped off and the weaving properties worsen. On the other hand, when the intrinsic viscosity of the core side polymer is increased, it is necessary to increase the intrinsic viscosity of the sheath side polymer as the intrinsic viscosity of the core side polymer increases, which results in higher crystallinity on the yarn surface and similarly worsening weaving properties. That is, the monofilament described in Patent Document 1 had a problem that weaving properties deteriorated when the strength was 6.0 cN / dtex or more.
[0008] Patent Document 2 also proposes a core-sheath composite monofilament, with a polymer having a lower intrinsic viscosity on the sheath side than on the core side, and a polymer having an intrinsic viscosity 0.3 or more lower on the sheath component than on the core component. Although it is true that by increasing the difference in intrinsic viscosity between the core polymer and the sheath polymer, it is possible to achieve both high yarn strength and weavability, when the core polymer and the sheath polymer are joined at the spinneret, the viscosity difference between the polymers makes it difficult to form the sheath component with an even thickness around the core component, which causes crimping of the yarn. In particular, in the case of high-mesh screen gauze and filters, the interval between adjacent warp yarns during warping is narrow, so that the yarn crimp causes it to become entangled with the adjacent yarns, causing warp yarn breakage and deteriorating warping properties. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2003-213528 A [Patent Document 2] Patent Publication No. 2010-77563 Summary of the Invention [Problem to be solved by the invention]
[0010] In order to obtain a composite polyester monofilament suitable for high-definition high-mesh filters and high-mesh screen gauze for high-precision printing, a monofilament with fineness (13.0 dtex or less), high strength (7.0 cN / dtex or more), and excellent warping and weaving properties is required.
[0011] In order to increase the strength, it is necessary to increase the draw ratio or the intrinsic viscosity of the core polymer, but if the crystallinity or orientation of the sheath polymer on the fiber surface becomes high, the yarn becomes more easily scraped and weaving properties deteriorate. On the other hand, if the difference in intrinsic viscosity between the core polymer and the sheath polymer is large, it becomes difficult for the sheath component to be formed in an even thickness around the core component, and the yarn crimps. In particular, when fine yarns are used to warp high-mesh screen gauze or filters, the intervals between adjacent warp yarns are narrow, so the crimped part of the yarn becomes entangled with the adjacent yarn, causing yarn breakage and worsening warping properties.
[0012] The present invention aims to overcome the above-mentioned problems and to provide a sheath-core composite monofilament which has high strength and high definition and also has excellent warping and weaving properties, which could not be obtained with conventional sheath-core composite polyester monofilaments. [Means for solving the problem]
[0013] The present invention for solving the above problems has the following configuration: A sheath-core composite monofilament having a sheath-core structure, with both the core and sheath components being polyester, characterized in that the fiber surface orientation I represented by formula (1) is 12.0 or less, and the variation coefficient T calculated by formula (2) is 0.11 or less when a total of eight radial lines are drawn at 45° intervals from the center point of the fiber cross section and the sheath thickness on each radial line is measured. I=I 1612 (Parallel) / I 1612 (vertical)...(1) I 1612 (Parallel): 1612 cm at change position parallel to fiber direction -1 Raman band intensity I 1612 (Vertical): 1612 cm at the change position perpendicular to the fiber direction -1 Raman band intensity T = standard deviation of sheath thickness at eight measurement points / average sheath thickness at eight measurement points (2) The sheath thickness at eight measurement points was determined by drawing eight radial lines at 45 degree intervals from the center point of the fiber cross section and measuring the sheath thickness on each radial line. Effect of the Invention
[0014] It is possible to provide a core-sheath composite polyester monofilament which is fine, has high strength, and is excellent in warping properties and weaving properties and is suitable for high-definition high-mesh filters and high-mesh screen gauze for high-precision printing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The core-sheath composite monofilament of the present invention will be described below. The core-sheath composite monofilament of the present invention is a core-sheath composite monofilament formed from two types of polyester.
[0016] The sheath-core type here refers to a sheath-core composite monofilament in which the core component is completely covered by the sheath component, resulting in a concentric sheath-core composite monofilament. The area ratio of the core component to the sheath component of the sheath-core composite monofilament is preferably 70:30 to 90:10, more preferably 80:20 to 85:15. If the core component is less than 70%, sufficient strength and modulus cannot be obtained. Conversely, if the sheath component ratio is less than 10%, the core component may be exposed by scraping during weaving, which may impair abrasion resistance.
[0017] The polyester used for the core-sheath composite monofilament of the present invention is a polyester mainly composed of polyethylene terephthalate (hereinafter referred to as PET). The PET used in the present invention is a polyester composed of 90 mol % or more of ethylene terephthalate repeating units, with terephthalic acid as the main acid component and ethylene glycol as the main glycol component.
[0018] However, it may contain a copolymerization component capable of forming other ester bonds at a ratio of less than 10 mol %. Examples of such copolymerization components include, for example, difunctional aromatic carboxylic acids such as isophthalic acid, phthalic acid, dibromoterephthalic acid, naphthalene dicarboxylic acid, and octoethoxybenzoic acid as acid components, difunctional aliphatic carboxylic acids such as sebacic acid, oxalic acid, adipic acid, and dimer acid as acid components, and dicarboxylic acids such as cyclohexane dicarboxylic acid as acid components, and examples of glycol components include, but are not limited to, ethylene glycol, diethylene glycol, propanediol, butanediol, neopentyl glycol, bisphenol A, cyclohexane dimethanol, and polyoxyalkylene glycols such as polyethylene glycol and polypropylene glycol.
[0019] Titanium oxide can be added as a shielding agent. By adding titanium oxide to the sheath component of the yarn surface layer, it is possible to obtain an effect of suppressing halation during screen printing and an effect of reducing yarn friction. If the amount of titanium oxide added to the sheath component is less than 0.1% by mass, sufficient halation suppression cannot be obtained, but if it is more than 1.0% by mass, a decrease in yarn strength and deterioration of spinnability occur, so the amount of titanium oxide added to the sheath component is preferably 0.1 to 1.0% by mass. Furthermore, it is more preferable to set the amount of titanium oxide added to the core polymer to 0.05% by mass or less, since this makes it possible to simultaneously increase the strength of the yarn, suppress halation, and reduce yarn friction. In addition, flame retardants, antistatic agents, ultraviolet absorbers, coloring pigments, etc. may also be added as necessary.
[0020] Next, the physical properties of the polyester monofilament of the present invention will be described. The polyester monofilament has a fineness of 3.0 dtex to 13.0 dtex, and more preferably 3.0 dtex to 8.0 dtex. By setting the fineness in this range, a high mesh filter or screen gauze of #350 (350 threads per inch = 2.54 cm) or more suitable for high-definition filters and high-precision printing can be obtained. Furthermore, by setting the fineness to 8.0 dtex or less, an even higher mesh can be achieved. The lower limit of the fineness is preferably 3.0 dtex or more in terms of weaving properties, particularly the flying property of the weft yarn in a sulzer type loom.
[0021] The strength is 7.0cN / dtex to 9.5cN / dtex, more preferably 8.0cN / dtex to 9.5cN / dtex, and the strength (modulus) at 10% elongation is 6.3cN / dtex to 9.0cN / dtex, more preferably 7.5cN / dtex to 9.0cN / dtex. If the strength is 7.0cN / dtex and the strength at 10% elongation is 6.3cN / dtex or less, misalignment occurs during weaving and printing, which induces fatal printing defects in screen printing applications with high printing accuracy. In addition, in the case of fine fineness varieties of 13dtex or less, there is a concern of fabric breakage due to insufficient strength. The upper limit is 9.5cN / dtex or less in strength and 9.0cN / dtex or less at 10% elongation from the viewpoint of scum during weaving.
[0022] The degree of orientation I (Equation 1) at 1 μm of the fiber surface layer is 12.0 or less, and more preferably 11.0 or less. By setting it to 12.0 or less, the orientation of the fiber surface layer is suppressed and sufficient abrasion resistance is obtained. The lower the value of the degree of orientation I, the better the abrasion resistance becomes, but on the other hand, it becomes difficult to obtain raw yarn strength. Therefore, it is important to set the degree of orientation I of the fiber surface layer to 12.0 or less while still satisfying the required raw yarn strength.
[0023] The sheath thickness variation coefficient T (Equation 2) is 0.11 or less, and more preferably 0.09 or less. By making it 0.11 or less, it is possible to suppress crimping of the yarn and prevent yarn breakage during the warping process. Furthermore, by making it 0.09 or less, yarn breakage does not occur even during warping of filters or screen gauze with an extremely high mesh count, and good warping properties can be obtained.
[0024] Next, a preferred method for producing the polyester monofilament of the present invention will be described. The intrinsic viscosity (IV) of the polyester of the core component is preferably 0.90 to 1.50. By making the intrinsic viscosity 0.90 or more, high strength and high modulus can be achieved, and by making it 1.50 or less, melt molding becomes easy. The intrinsic viscosity of the polyester used for the sheath component is lower than that of the polyester of the core component, and is preferably 0.40 to 0.70. By setting the intrinsic viscosity at 0.40 or more, stable spinnability can be obtained. The intrinsic viscosity is more preferably 0.50 or more. In order to obtain good abrasion resistance, i.e., scum resistance, the intrinsic viscosity is preferably 0.60 or less.
[0025] In addition, the difference in intrinsic viscosity between the core polymer and the sheath polymer is preferably 0.30 to 1.00. By making the difference in intrinsic viscosity 0.30 or more, the orientation degree and crystallinity of the polyester of the sheath component, i.e., the surface of the core-sheath composite monofilament fiber, can be suppressed even during spinning of high-strength yarn, and good weaving properties can be obtained. In addition, by making the difference in intrinsic viscosity 1.00 or less, the orientation of the sheath component proceeds appropriately, and high strength can be obtained. More preferably, it is 0.50 to 0.80.
[0026] The core-sheath composite monofilament of the present invention is obtained by melting and extruding a polymer using a spinning machine, sending it to a specified spinning pack, filtering the polymer in the pack, and then spinning it out from a spinneret.
[0027] When spinning a core-sheath composite monofilament, a sheath polymer discharge hole is provided around the core polymer discharge hole in the spinneret, and the core and sheath polymers are bonded together to obtain a core-sheath composite cross section. However, when the intrinsic viscosity difference between the core polymer and the sheath polymer is 0.3 or more, especially 0.5 or more, the cross section formability of the sheath polymer deteriorates, and the thickness of the sheath polymer around the core polymer becomes non-uniform, causing crimping of the yarn. In addition, when spinning a fine fiber of 8.0 dtex or less, the original sheath thickness is thin, so the non-uniformity of the sheath thickness increases relatively, and crimping occurs more significantly. Crimping induces yarn breakage during warping and significantly reduces warping. To suppress crimping, it is important to improve the cross section formability of the sheath polymer.
[0028] Specifically, by setting the number of sheath component discharge holes arranged around the core component discharge holes to 4 or more, more preferably 6 or more, the thickness variation of the sheath component can be suppressed, making it possible to suppress crimping. On the other hand, if the sheath has 10 or more discharge holes, the discharge amount of sheath polymer per hole decreases, making it difficult to stably discharge the sheath polymer, and causing the sheath thickness to become non-uniform, so the upper limit for the number of sheath polymer discharge holes is 10.
[0029] To obtain the core-sheath composite monofilament of the present invention, the polyesters of the core component and the sheath component are each melted using a composite spinning machine, and a specified amount is sent to a composite spinning pack by a metering pump through the polymer piping for the core component and the sheath component, and after both polymers are filtered in the spinning pack, the composite is spun into a core-sheath cross-sectional shape using a spinneret.
[0030] The filament can be produced by any method, such as a two-step method in which the filament discharged from the spinneret is once wound up as an undrawn filament and then drawn, or a direct spinning and drawing method in which the filament discharged from the spinneret is subsequently drawn without once being wound up. However, a direct spinning and drawing method in which drawing is performed directly in connection with the spinning process is preferred in order to reduce the number of guides through which the filament passes during the production process and to suppress filament sheathing.
[0031] The core-sheath composite monofilament of the present invention thus obtained has a fineness and high strength, and further has excellent warping and weaving properties, and is extremely suitable as a constituent material for high-definition high-mesh filters and high-mesh screen gauze for high-precision printing. EXAMPLES
[0032] The present invention will be described in more detail below with reference to examples. Measurements in the examples were measured by the following methods.
[0033] 1. Intrinsic viscosity (IV) The definition of ηr was determined by dissolving 0.8 g of the sample polymer in 10 mL of o-chlorophenol (hereinafter referred to as OCP) with a purity of 98% or higher at 25°C, and calculating the relative viscosity ηr using an Ostwald viscometer at 25°C using the following formula to calculate the intrinsic viscosity (IV). ηr=η / η0=(t×d) / (t0×d0) Intrinsic viscosity (IV)=0.0242ηr+0.2634 Here, η is the viscosity of the polymer solution, η0 is the viscosity of the OCP, t is the time it takes for the solution to fall (sec), and d is the density of the solution (g / cm 3 ), t0: OCP fall time (sec), d0: OCP density (g / cm 3 )
[0034] 2.Fineness A 500 m length of yarn was spooled, and the mass (g) of the spool was multiplied by 20 to obtain the fineness.
[0035] 3. Breaking strength (cN / dtex) and strength at 10% elongation (modulus) (cN / dtex) Measurements were performed using Orientec Tensilon UCT-100 in accordance with JIS L1013 (1999).
[0036] 4. Degree of fiber surface orientation A Horiba Jobin Yvon Laser Raman Spectrometer T-64000 was used, and an argon ion laser (wavelength: 514.5 nm, laser power: 60 mW) was used as the light source, and the light was focused to 1 μm using a 100x objective lens. Raman scattering light was detected by a CCD detector under the conditions of single mode, slit 100 μm, and diffraction grating 1800 gr / mm. The sample was embedded in resin (bisphenol-based epoxy resin, cured for 24 hours) and then sectioned using a microtome. The thickness of the section sample was 2 μm, and the cut was made elliptical by tilting it 3° from the fiber axis. The laser was focused at a point 1 μm from the fiber surface, and the average value of n = 5 measurements was used to calculate the orientation degree I from the calculation formula (1). I=I 1612 (Parallel) / I 1612 (vertical)...(1) I 1612 (Parallel): 1612 cm at change position parallel to fiber direction -1 Raman band intensity I 1612 (Vertical): 1612 cm at the change position perpendicular to the fiber direction -1 Raman band intensity
[0037] 5. Coefficient of variation of sheath thickness A cross-sectional photograph of the fiber was taken using a Keyence VHX-7000 optical microscope. Three points were then specified on the outer periphery of the photographed cross-sectional photograph of the fiber to determine the center point of the fiber cross-section. A total of eight radial lines were drawn from the center point at 45 degree intervals, and the sheath thickness on the eight radial lines was measured. The coefficient of variation T shown in (2) was calculated from the average value and standard deviation of the sheath thickness at the eight measurement points. T = standard deviation of sheath thickness at eight measurement points / average sheath thickness at eight measurement points (2)
[0038] 6. Warping The core-sheath composite monofilaments of each of the examples and comparative examples of the present invention were used as warp yarns, and warping was performed at a yarn speed of 200 m / min for a width of 2 m and a length of 300 m. Warping was performed with the following mesh numbers depending on the fineness. 18T: 300 pieces / 2.54cm 13T: 350 pieces / 2.54cm 8T: 420 pieces / 2.54cm 4T: 500 pieces / 2.54cm The warping property was evaluated based on the degree of shrinkage of the yarn and the frequency of yarn breakage, and a grade of B or above was deemed to be acceptable. A: Very good (there is very little shrinkage of the yarn, and yarn breakage during warping hardly occurs) B: Good (thread crimping is observed, but there is little thread breakage during warping, and the product is still at a production level) C: Inferior (Strong shrinkage of yarn is observed. During warping, yarn breakage occurs frequently due to entanglement with adjacent yarns, making warping impossible.)
[0039] 7.Weavability Using core-sheath composite monofilaments of each of the examples and comparative examples of the present invention for both the warp and weft, screen gauze with the following mesh numbers according to fineness was woven on a Sluzer type loom at a loom rotation speed of 200 rpm. 18T: 300 pieces / 2.54cm 13T: 350 pieces / 2.54cm 8T: 420 pieces / 2.54cm 4T: 500 pieces / 2.54cm The degree of dirt on the weaving reed was noted and the weaving performance was judged according to the following index, with a grade of B or above being considered a pass. A: Very good (almost no scum stains) B: Good (slight staining of the reed due to scum is observed, but still at a level that allows production) C: Inferior (Continuous weaving is not possible due to reed stains caused by scum, making production impossible)
[0040] 8. Printing accuracy The core-sheath composite monofilaments of each of the examples and comparative examples of the present invention were used for both the warp and weft, and a screen gauze with the following mesh numbers was woven using a Sluzer type loom at a rotation speed of 200 rpm. 18T: 300 pieces / 2.54cm 13T: 350 pieces / 2.54cm 8T: 420 pieces / 2.54cm 4T: 500 pieces / 2.54cm After that, a pattern of 50 lines spaced 50 μm apart was formed on the resulting mesh fabric using a photosensitive emulsion, and the printed condition was checked and evaluated by a skilled inspection technician, with a grade of B or above being deemed a pass. S: Very good (line pattern reproduction is very good) A: Good (very minor printing defects, but sufficient for high-definition screen printing applications) B: Fair (minor printing defects are observed, but the level is acceptable for high-definition screen printing applications) C: Inferior (poor line reproducibility, not suitable for high-definition screen printing applications)
[0041] Example 1 A polyester with an intrinsic viscosity of 0.95 and a titanium oxide content of 0.5% by mass as the core component and a polyester with an intrinsic viscosity of 0.50 and a titanium oxide content of 0.5% by mass as the sheath component were melted at a temperature of 295°C using an extruder, and then pumped to a composite ratio of core component:sheath component = 80:20 at a polymer temperature of 280°C, and flowed into a spinneret to form a core-sheath type. At the joining point of the core component and sheath component in the spinneret, four sheath component outlet holes were provided around the core component outlet hole, and the core component and sheath component were joined.
[0042] The sheath-core composite monofilament discharged from the spinneret was actively heated and kept warm by a heater so that the atmospheric temperature directly below the spinneret was 290°C, then cooled by a yarn cooling fan, oiled by an oiling device, and taken up at a speed of 556 m / min, then appropriately stretched (stretch ratio 5.4 times) to the desired strength without winding, heat-treated at 190°C with a final stretching roller, and wound up at a speed of 3000 m / min with a yarn winding device to obtain a sheath-core composite monofilament with a fineness of 8.0 dtex. The evaluation results are shown in Table 1, and the warping and weaving properties were extremely good, and the printing accuracy was at an acceptable level for high-definition screen printing applications, although minor printing defects were observed.
[0043] Example 2 A core-sheath composite monofilament was obtained in the same manner as in Example 1, except that a polymer with an intrinsic viscosity of 1.2 and a titanium oxide content of 0.5% by mass was used as the core component, and the stretch ratio was changed to 5.8 times. The evaluation results are shown in Table 1. Along with the improvement in yarn strength and modulus, the printing accuracy was improved compared to Example 1. On the other hand, the increase in the stretch ratio promoted the orientation of the fiber surface, and slight reed staining was observed during weaving, but it was at a level that was still producible.
[0044] Example 3 A core-sheath composite monofilament was obtained in the same manner as in Example 2, except that the amount of polymer discharged was changed and the fineness was changed to 4.0 dtex. The evaluation results are shown in Table 1. By changing the fineness to 4.0 dtex, a high mesh size of the screen gauze was achieved, and extremely good printing accuracy was obtained.
[0045] Example 4 A sheath-core composite monofilament was obtained in the same manner as in Example 3, except that the titanium oxide content of the core polymer was 0 mass % and the draw ratio was 5.6 times. The evaluation results are shown in Table 1. By not including titanium oxide in the core polymer, the yarn strength was improved, and even when the draw ratio was reduced from 5.8 to 5.6 times, a sheath-core composite monofilament with physical properties equivalent to those of Example 3 was obtained. By reducing the draw ratio, the orientation of the fiber surface was suppressed, and as a result, weaving properties were improved compared to Example 3.
[0046] Comparative Example 1 A core-sheath composite monofilament was obtained in the same manner as in Example 1, except that a polymer with an intrinsic viscosity of 0.8 and a titanium oxide content of 0.5% by mass was used for the core component, and the draw ratio was changed to 4.8 times. The evaluation results are shown in Table 1. Good results were obtained for warping and weaving properties, but the yarn strength and 10% modulus were lower than those of Example 1 due to the lowering of the intrinsic viscosity and draw ratio of the core component polymer. As a result, misalignment of the gauze occurred during weaving and printing, and the printing accuracy was significantly deteriorated, to a level that was not suitable for high-definition screen printing applications.
[0047] Comparative Example 2 A core-sheath composite monofilament was obtained in the same manner as in Example 1, except that a polymer with an intrinsic viscosity of 0.8 and a titanium oxide content of 0.5% by mass was used for the sheath component, and the draw ratio was changed to 5.1 times. The evaluation results are shown in Table 1. By increasing the intrinsic viscosity of the sheath component polymer from 0.5 to 0.8, a core-sheath composite monofilament with physical properties equivalent to those of Example 1 was obtained even when the draw ratio was reduced from 5.4 to 5.1 times. However, the increased crystallinity of the sheath component polymer on the yarn surface significantly deteriorated weaving properties, making it impossible to produce gauze.
[0048] Comparative Example 3 A sheath-core composite monofilament was obtained in the same manner as in Example 1, except that a polymer with an intrinsic viscosity of 0.8 and a titanium oxide content of 0.5% by mass was used as the core component, and the draw ratio was changed to 6.2 times. The evaluation results are shown in Table 1. Since the intrinsic viscosity of the core component polymer was reduced from 0.95 to 0.8, it was necessary to increase the draw ratio from 5.6 to 6.2 times in order to obtain a sheath-core composite monofilament with the same physical properties as in Example 1. As a result, the orientation of the fiber surface progressed, weaving properties were significantly deteriorated, and it was impossible to produce gauze.
[0049] Comparative Example 4 A core-sheath composite monofilament was obtained in the same manner as in Example 2, except that the polymer discharge amount was changed to change the fineness to 18.0 dtex, and the number of discharge holes for the sheath component around the discharge hole for the core component in the spinneret was changed to three holes. The evaluation results are shown in Table 1. Since the fineness was 18.0 dtex, weaving with a 300 mesh was the limit, and the printing accuracy was not suitable for high-definition screen printing applications. In addition, crimping of the yarn was confirmed, although it was at a level that allowed warping.
[0050] Comparative Example 5 A core-sheath composite monofilament was obtained in the same manner as in Example 3, except that the number of sheath component discharge holes around the core component discharge hole in the spinneret was changed to three holes. The results are shown in Table 1. By changing the number of sheath component discharge holes to three holes, the thickness of the sheath component became non-uniform, and the yarn was severely crimped. When this yarn was fed into warping, many yarn breaks occurred during warping due to entanglement with adjacent yarns, making warping impossible.
[0051] Comparative Example 6 A core-sheath composite monofilament was obtained in the same manner as in Example 3, except that the number of sheath component discharge holes around the core component discharge hole in the spinneret was changed to 12 holes. The results are shown in Table 1. The discharge amount of sheath polymer per hole was reduced, making the discharge of the sheath polymer unstable and the thickness of the sheath component non-uniform. As a result, severe crimping was confirmed in the yarn, and yarn breakage occurred frequently during warping, making it impossible to carry out warping.
[0052] [Table 1]
Claims
1. A sheath-core composite monofilament in which both the core component and the sheath component are polyester in a core-sheath composite cross section, and which satisfies the following (a) to (e): (a) Fineness 3.0 to 13.0 dtex (b) Strength 7.0-9.5cN / dtex (c) Strength at 10% elongation: 6.3 to 9.0 cN / dtex (d) The degree of orientation I at 1 μm of the fiber surface layer, expressed by the formula (1), is 12.0 or less. I=I 1612 (Parallel) / I 1612 (Vertical)...(1) I 1612 (Parallel): 1612 cm at a change position parallel to the fiber direction -1 Raman band intensity I 1612 (Vertical): 1612 cm at the change position perpendicular to the fiber direction -1 Raman band intensity (e) The coefficient of variation T of the sheath thickness, expressed by the formula (2), is 0.11 or less. T = standard deviation of sheath thickness at 8 measurement points / average value of sheath thickness at 8 measurement points (2)
2. 2. The core-sheath composite monofilament according to claim 1, wherein the titanium oxide content of the core polyester is 0.05% by mass or less when the titanium oxide content of the core polyester is measured according to JIS L1013.
Citation Information
Patent Citations
Sheath / Core conjugate polyester monofilament for screen gauze and method for producing the same
JP2003213528A
Polyester monofilament
JP2010077563A